The Role Of Productive Zakat In Community Economic Empowerment In Baznas Jepara District - Devi, Sifana; Silviana Pebruary (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Badan Amil Zakat Nasional (BAZNAS) is a zakat management institution established by the government which has the task of collecting, distributing and utilizing zakat. Zakat as an important aspect in economics, especially when approached from a scientific aspect and institutionally can be a solution to alleviate poverty because it plays a role in empowering the community, especially the poor, the dhuafa’, and others. The main problem in this study is how the role of productive zakat in the economic empowerment of the community in BAZNAS, Jepara Regency and how the economic development of the people who receive the assistance. This research is qualitative research using descriptive analysis. Data collection in this study was through observation, interviews with interested parties in this case BAZNAS Jepara Regency and some mustahik and documentation. The results of this study show that the role of productive zakat in community economic empowerment in BAZNAS Jepara Regency has been successful, this can be seen from the results of empowerment such as reducing poor people, improving socio-economic living standards, fostering the spirit of help, independence and others. However, in developing the business, some mustahik have not been realized properly due to lack of assistance.